Το πρότυπο του επεισοδίου του Χαρίδημου (Ερωτόκριτος B 591-744): Ariosto ή Tasso; - Πασχάλης Μιχαήλ (Σύγκριση/Comparaison/Comparison, 2020)
The model of the Charidimos episode (Erotokritos B 591-744): Ariosto or Tasso; It is well known that Vitsentzos Kornaros based the story of Charidimos, who accidentally killed his wife during a hunting expedition (Erotokritos B 591-744) on some version of the mythical narrative of Cephalus and Procris as told by Ovid in Metamorphoses 7.796-865. As regards the circumstances of the death of Charidimos’ wife, Kornaros reworked the initial idea in such an original fashion that it differs from all versions of the same story or reconfigurations of it. The only certainty we have is that Charidimos’ decision to take part in jousts and offer the prizes he wins to the tomb of his beloved was inspired by the story of Rodomonte and Isabella in Ludovico Ariosto’s Orlando furioso, canto 29. As regards the possible association of the Charidimos episode with another modern reworking of the Cephalus and Procris narrative in Torquato Tasso’s Rinaldo 7.16-51, which was suggested by Eirini Lydaki in 2015, the most notable similarity with the Erotokritos version is the substitution of a real woman for Ovid’s “aura”. Kornaros, however, handled the third party in his story (a beautiful shepherdess) in such an original fashion that the existence of Tasso’s Ermilla, a beautiful virgin huntress and constant companion of the anonymous knight during his hunting expeditions, does not contribute in any significant way to our understanding of the Erotokritos episode.